RDPLF 2022 annual report: Profile of home hemodialysis patients in Belgium and Francel (synthetic raw results) - Christian Verger; Emmanuel Fabre (RDPLF, 2023)
We present primary descriptive data in the form of tables and graphs for patients treated with home hemodialysis in France and French-speaking Belgium in 2022. These data were recorded in the database of the French-speaking Register of Peritoneal Dialysis and Home Hemodialysis (RDPLF). The average age of the patients is similar in both countries: 52.7 years in France and 54.7 years in Belgium. The percentage of patients with diabetes is 25.6% in Belgium and 18.5% in France. The majority of patients undergo daily hemodialysis 5 to 7 times per week. Of the patients, 11% have received peritoneal dialysis in the past. Of these, 23.5% transitioned to home hemodialysis less than 3 months after stopping peritoneal dialysis, while 23.6% transitioned after 2 years of center-based or self-administered hemodialysis. Practices differ between Belgium and France. In Belgium, a central catheter is used in 57.5% of cases, compared to 8.5% in France. For arteriovenous fistula puncture, the buttonhole technique is used in 91% of cases in Belgium and 47.8% of cases in France. In Belgium, 70% of patients dialyze independently, while in France, 71% of patients dialyze in the presence of a family member. The main cause of treatment discontinuation is transplantation (44% of technical dropout).